Blind Man's Bluff - Sharpe, Jon (Sharpe, Jon. Renegade rifles., 2012)
The Chiricahua Mountains are full of dangers-- and the most terrifying is Apache warrior Red Dog. Skye Fargo rescues a prospector being tortured by Red Dog, which earns him the Apache's hatred.